Mobile cloud security a Survey (International Journal of Engineering and Computer Science, 2014)
Cloud computing has become part day today life. There are large numbers of vendors providing different cloud offerings. With the evolution of mobile devices, mobile cloud computing has drawn attention. Even though cloud security is a well thought aspect, there is need to look at cloud security from a mobile device perspective. In this paper we have analyzed different research happenings in this area and presented future research needs.